2011
DOI: 10.1016/j.ijdevneu.2011.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine inflammation, insufficient to induce parturition, still evokes fetal and neonatal brain injury

Abstract: Exposure to prenatal inflammation is a known risk factor for long term neurobehavioral disorders including cerebral palsy, schizophrenia, and autism. Models of systemic inflammation during pregnancy have demonstrated an association with an immune response an adverse neurobehavioral outcomes for the exposed fetus. Yet, the most common route for an inflammatory exposure to a fetus is from intrauterine inflammation as occurs with chorioamnionitis. The aims of this study were to assess the effect of intrauterine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
173
1
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(194 citation statements)
references
References 115 publications
11
173
1
4
Order By: Relevance
“…In particular, the absence of basal IL-1β responses in our present study contrast with the marked IL-1β elevations in neonatal brains following exposure to intrauterine LPS reported by Elovitz et al (12). These differences may reflect the more direct fetal effects of intrauterine inflammation compared to the generalized maternal exposure in our studies.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…In particular, the absence of basal IL-1β responses in our present study contrast with the marked IL-1β elevations in neonatal brains following exposure to intrauterine LPS reported by Elovitz et al (12). These differences may reflect the more direct fetal effects of intrauterine inflammation compared to the generalized maternal exposure in our studies.…”
Section: Discussioncontrasting
confidence: 95%
“…Previous studies have shown a potentiating effect of intrauterine LPS on inflammatory cytokines in fetal and neonatal brains (12). In the present study, basal brain interleukin (IL)-1β mRNA expression was similar in LPS-exposed and control neonates, and SeV infection only moderately increased IL-1β expression in both groups (Figure 4).…”
Section: Maternal Inflammation Alters Sev-induced Neonatal Brain Il-4supporting
confidence: 67%
“…Clinical chorioamnionitis and puerperal endomyometritis are the leading causes of infection-related complications in pregnant women. In addition to the maternal morbidity associated with clinical chorioamnionitis and puerperal infections, neonates born to mothers with clinical chorioamnionitis at term (TCC) are at increased risk for long-term complications, notably cerebral palsy (11)(12)(13).…”
Section: Clinical Definitionsmentioning
confidence: 99%
“…Control groups (Negative control group): Dams received either saline injections (100 ul) on GD15 (n=5), or no injections (n=5). Term delivery was defined as delivery after 19 days of gestation (27). All the animals were observed until spontaneous delivery.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…An intraperitoneal E. Coli LPS model was used to induce pretenn delivery in mice to model systemic inflammation with chorioamni onitis. A high dose of LPS (50llglmouse) was chosen based on our findings and previous studies using various doses ofLPS (20,21,27,30), in order to ensure consistent pretenn delivery (90% pretenn delivery) . The dams in the LPS group that delivered prematurely delivered within 24 h after LPS injection compared to the dams A .. .~.…”
Section: H Istopathologymentioning
confidence: 99%